The group rehabilitation helped me adjust to a new life: Experiences shared by persons with an acquired brain injury. (May 2013) - Lexell, Eva Månsson; Alkhed, Ann-Kristin; Olsson, Kerstin
<x xml:space="preserve">Abstract</x> Primary objective: The aim of this study was to describe how persons with acquired brain injury experience an out-patient group rehabilitation programme and how the programme had contributed to their everyday lives. Design and method: Qualitative interviews with 11 men and women with an acquired brain injury who had participated in an out-patient group rehabilitation programme were performed. Data was analysed with qualitative content analysis. Findings: The findings formed the theme 'The group rehabilitation helped me adjust to a new life' that revealed experiences related to the content and outcome of the programme, as well as the process they went through during the programme. The participants described how the rehabilitation gave them the tools they needed to change their everyday lives, especially in relation to improved knowledge and learning new routines and habits. They perceived their rehabilitation as a long-term, individual, but also collaborative process, where professionals as well as family and friends had crucial roles. Conclusion: Learning how persons with acquired brain injury experience participation in a group rehabilitation programme can help to unravel parts of the 'black box of rehabilitation' and can support professionals to better understand the effective components of such programmes.